1997
DOI: 10.1111/j.1365-2923.1997.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Rewards for teaching excellence: practice in South African medical schools

Abstract: Excellence in teaching through recruitment of good teachers, rewarding good teaching and the creation of staff development programmes are priorities in the mission statement of most universities. Often, reality belies intention. At many universities serious attempts to ensure maximum teacher effectiveness, overt recognition of teaching excellence, and specific development funding are lacking. This study examines the extrinsic (i.e. financial) reward systems which operate at the eight medical schools attached t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…It has been asserted that the best way to motivate professors to improve their teaching is by creating an equitable system of rewards for excellence and effectiveness in teaching (Gibbs, 1995;Olmesdahl, 1997;Young, 2006). Empirical studies have also affirmed the positive impact of teaching awards on enhancing the quality of teaching and recognition of teaching in higher education institutions (Brawer, Steinert, St-Cyr, Watters, & Wood-Dauphinee, 2006; Sorcinelli, & Davis, 1996).…”
Section: Barriers For Teaching Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been asserted that the best way to motivate professors to improve their teaching is by creating an equitable system of rewards for excellence and effectiveness in teaching (Gibbs, 1995;Olmesdahl, 1997;Young, 2006). Empirical studies have also affirmed the positive impact of teaching awards on enhancing the quality of teaching and recognition of teaching in higher education institutions (Brawer, Steinert, St-Cyr, Watters, & Wood-Dauphinee, 2006; Sorcinelli, & Davis, 1996).…”
Section: Barriers For Teaching Improvementmentioning
confidence: 99%
“…Universities should stop creating any incentives or rewards that link hiring and promotion to research and undervalue teaching (Tagg, 2012) if they expect to see change in the quality of teaching. Similarly, Olmesdahl (1997) acknowledges the importance of equitable system of rewards for excellence and effectiveness in teaching. Other studies have revealed a positive impact and the significance of teaching awards on enhancing the quality of teaching and recognition of teaching in higher education institutions (Brawer et al, 2006;Sorcinelli & Davis, 1996).…”
Section: Do We Need Rewards and Endowment For Teaching Quality?mentioning
confidence: 99%
“…Since new pedagogies such as PBL require a realignment of the roles of students and staff, traditionalists may resist the change as it threatens their authority and status. There is consensus that in preparing faculty for PBL, considerable time and energy need to be devoted to training staff for their new roles as educators and facilitators (Olmesdahl 1997;Mennin & Krackov 1998;Harden 1999;Bernier et al 2000;Bland et al 2000;Murray & SavinBaden 2000;Farmer 2004). Even experienced facilitators have identified a need for continuous support and training (Tremblay et al 2001).…”
Section: Practice Pointsmentioning
confidence: 99%
“…The problem of how to provide incentive for teaching of m edical students has been recognized for m any years (Krause, 1977;de Saintonge, 1993;Finucane et al, 1994;Finucane & Rolfe, 1996;Gerrity et al, 1997), and schemes such as ® nancial inducement or local recognition awards have been introduced with some success (Joyce, 1975;Greer, 1990;Gastel, 1991;Posluns et al, 1990;Olmesdahl, 1997), but have never become widely adopted.…”
Section: Comm Entmentioning
confidence: 99%